Evaluation of the cooperation between the European Community and the Caribbean ACP-States (German Development Institute BerlinDE, 1985)
Reviews origins and execution, financing, reorientation activities and output of the CARICOM/EDF Export Promotion Project and evaluates its efficiency, effectiveness and impact on regional firms. Makes recommendations pertaining to role of the Caricom Secretariat and need for a more clearly defined regional export promotion policy. Annex 2 contains draft interim review of the project.
Includes bibliographical references